Checklist of helminth parasites of threatened vertebrate species from Brazil - Muniz-Pereira, Luís C.; Vieira, Fabiano M.; Luque, José L. (Zootaxa, 2009)
Using available records, unpublished information retrieved from the Helminthological Collection of the Oswaldo Cruz Institute (CHIOC) and published reports, a checklist of the recorded helminth parasites of endangered vertebrates from Brazil was generated. A total of 772 records and 186 helminth species (6 Acanthocephala, 83 Nematoda, 23 Cestoda, 64 Trematoda, 10 Monogenea) in 76 host species (7 Actinopterygii, 8 Chondrichthyes, 1 Amphibia, 10 Reptilia, 22 Aves, 28 Mammalia) from Brazil were listed in the present work, including 39 undetermined helminth species and 10 new host records. This is the first compilation of the helminth parasites of threatened vertebrates in Brazil and in the Neotropics.